Comparativo uniforme de rendimiento con Variedades y Líneas de Maní (Arachis hipogaea L) en la estación experimental "El Porvenir" - Juan Guerra - Ramírez Navarro, Esther (2003)
The present investigation work was carried out in the Experimental Station ''The Future"-Institute of Agrarian Investigation. District of Juan Guerra, County and Department of San Martín, with a geographical location of a Longitude west of 76° 20, south latitude of 6º24"y an altitude of 356 m.s.n.m., having like an area of life of Bs-tropical. The present work had as objectives to determine the variety y/o promissory line of peanut of more yield and adaptation to Juan Guerra area and to determine the cost benefit of the variety y/o line but excellent, proving 11 lines and 3 varieties (witness). The work began June 10 1998 with the siembra of the peanut placing two seeds for blow, to a distancing of 60 cm between arrays and 20 cm among plants, having like design of Complete Block Randomizado with 14 treatments and 03 repetitions and evaluating 12 parameters according to the methodology of the work. It was obtained results that they demonstrate us that there were lines with characteristic and different behaviors, this way being able to obtain that the treatment 9 denominated 506-1-203-313 had a yield of 3 876 kglha and he/she has adaptation to the area compared with the yields of the other treatments, as well as for example the Tl with 3 471 Kg, the T8 with 3 424 Kg, the TI with 3 232 Kglha.